Effect of peer tutoring instruction materials on students' achievement in some physics concept: A study in school effectiveness (2010)
Without the knowledge of physics, discovery of hydro-electric power, gas turbine, thermo-nuclear power plant, submarine, aeroplane, jet fighter, intercontinental ballistic missile, x-ray in the treatment of cancer, constructions of telephone, ICT, diodes, valves, rectifiers, amplifiers, intergrated and logic circuits which are widely used in electronic systems and computers would have been impossible. Unfortunately, students are not registering for physics and those who register are not performing well in the subject. Many attempts were made to correct the abnormality; yet, the desired outcomes have not been achieved, probably because there are no enough physics teachers in schools. Therefore, this study is designed to find the effect of peer tutoring instructions on students' achievement in some physics concepts. A 2x2 quasi-experimental, pre-test, post-test, control group factorial design was used for the study. The samples used in this study were 161 SS1 Physics students selected from four stratified randomly selected secondary schools in Ibadan Municipal. Data obtained were analysed using mean, standard deviation and Analysis of Covariance (ANCOVA). The results shows that students in the peer tutoring instructions perform better in physics achievement test than their counterparts in the control group. Students with high mathematical ability performed better than their counterparts with low mathematical ability. Therefore, for effective teaching, learning, understanding and mastering physics concepts, the use of peer-tutoring is recommended for the physics teachers and students.